Upaya Peningkatan Hasil Belajar Siswa pada Materi Operasi Hitung Pecahan Desimal Menggunakan Alat Peraga di Kelas VA SD Negeri 29 Banda Aceh - Monawati Monawati; Fauzi Fauzi; Rosma Elly; Suci Fitriani (Universitas Syiah Kuala, 2021)
Mathematics is concerned with abstract ideas and concepts arranged hierarchically and deductive reasoning. In this study, researchers used teaching aids to improve student learning outcomes in mathematics in the decimal fraction count operations material. The props used are Block Dienes, place value cards, and abacus. The formulation of the problem in this study is